Mutu Jagung yang Diperdagangkan di Kota Jambi Diukur Berdasarkan Nilai Bulk Density dan Kandungan Serat Kasar - S Fakhri; Y Zaharanova; M Afdal (Politeknik Negeri Lampung, 2023)
Maize is being used as the main energy source in poultry feed in Indonesia. The authorities therefore, must guarantee that the maize available in markets must meet Indonesian quality standards. Determination of maize quality standards is still based on nutrient contents obtained through chemical analysis, which is very expensive and time consuming. The purpose of this study was to evaluate the quality of maize based on the bulk density (BD) value and crude fiber (CF) content of maize, these two parameters were then correlated to obtain the prediction equation. Samples were taken from 17 poultry shops (PS) of Jambi City and were divided into 3 groups based on sales turnover scale (large, medium, small). Each scale represented by 6 PS. Pure maize was used as a control. A total of 3 kg of maize samples was randomly taken from each PS represented by 3 sacks of maize.Obtained samples were subjected to BD measurement and CF analysis. The results showed that BD and CF of maize were not affected by sales turnover scale. There was adulteration of maize cobs in a proportion of 6.78, 7.67 and 15.47% in granulated, crushed and ground maize, respectively. The quality of maize traded at Jambi City was not affected by sales turnover scale. The chemical quality of maize as reflected by CF content (Y, %) can be predicted from BD (g/ml) according to this equation Y= -0.0285X + 21.83, r2= 0.65.